Problemas y Soluciones - Nieto, José; Tipe, Jorge (Universidad Antonio Nariño, 2022)
The goal of this section is to present interesting mathematical problems andits solutions. We invite the readers to propose problems which may be tackled byhigh school or college students without specialized knowledge.